Sistem Informasi Persediaan Obat dengan Metode Naïve Bayes Pada RSUD Tanjungpinang - Isron Al Miraz Siregar; Elvianna; Nurul Saepul (Jurnal Bangkit Indonesia, 2018)
The integrated data processing system at the Tanjungpinang Hospital Pharmacy cannot predict the stock of drugs. Drug data prediction system is based on drug sales and drug sales rates. The reason for using the naïve Bayes method is because this method makes it easy to calculate and determine the possibilities that occur at the Tanjungpinang Hospital pharmacy and can help the pharmacy in making decisions to make drug purchase transactions. The development of information systems in making software uses the Waterfall method. The development application uses netbeans 7.3.1 and MySQL as the database. The program was tested using the Black Box method. With this application, it can help the pharmacy to collect drug data quickly and accurately and can help predict drug data using the naïve Bayes method to make decisions in making drug purchases. And can make a report which will be submitted to the owner.